Designing A Solar Charge Pack Battery Management System Integration for Enhanced Charging Performance - Zou, Muhammad Ezam Anwar; Ismail, Muhammad Nafis (Evolution in Electrical and Electronic Engineering, 2024)
This study aims to improve the current portable solar charge pack by implementing battery management system to enhanced the charging performance by increasing the lifespan of the battery and safety. The study also aims to improve the previous solar powered backpack that has limited power production because of the low efficiency in converting sunlight energy into electricity during travelling by implementing manually adjustable tilt angle mechanisms to help increase the solar panel efficiency during travelling. This project will use solar panel attached to a backpack using manually adjustable tilt angle mechanisms, then it will be connected to solar charger controller and battery management system that has been designed for the battery. Lastly, it will be connected to a USB power output to charge electronic device. The result will be simulation for comparison of charging circuit with and without cell balancer for three batteries in series. This simulation shows that the charging circuit with BMS has balanced soc percentage between the battery and the voltage does not exceed the battery full voltage. Next, the comparison of power generated by solar power at different tilt angle. The manually adjustable tilt angle has been proven to increase power generated by solar panel.